Terapi Paschimottanasana dan Adho Mukha Padmasana terhadap Intensitasnyeri pada Remaja Putri yang Mengalami Dismenore Primer - Putu Wahyu Sri Juniantari Sandy; I Wayan Sujana; Aditha Angga Pratama (LPPM STIKES KENDAL, 2020)
Teenagers after menarch always complain of the pain felt during menstruation. This makes him uncomfortable, sick and not even concentrating in class lessons. Many of the absence of young women at school due to not being able to withstand pain during menstruation. So that there is a need for complementary therapy by implementing yoga Paschimottanasana and Adho Mukha Padmasana. The purpose of this study was to assess differences in pain intensity in young women who were given postchimonttanasana therapy and Adho Mukha Padmasana with those who were only given conventional knowledge and therapeutic information. The quantitative research method used a quasi-experimental design with a pretest-posttest control group design. The population was all young women in SMA Negeri 3 Singaraja with a minimum sample of treatment and control groups of 188 respondents. Sampling with stratified random sampling technique in class 10-12. Provision of yoga was given to the treatment group then assessed pre and posttest using the Verbal Descriptor Scale / VDS questionnaire that was valid and reliable Analysis using univariate and bivariate analysis with paired t-test and independent t-test statistical tests. The results of statistical tests using paired t-test there were differences in pain intensity between before and after from the treatment group (p value 0.001) while in the control group there was no difference. Judging from the effect of using the independent t-test, it was found that Paschimottanasana yoga and Adho Mukha Padmasana had an effect on reducing the intensity of pain during menstruation 1.22 (0.517-1.911) with a p value <0.05 than those not only given conventional knowledge and therapy. The conclusion is that there is a difference and the effect of reducing the intensity of pain from giving yoga Paschimottanasana and Adho Mukha Padmasana.